Wild guppies from populations exposed to higher predation risk exhibit greater vasotocin brain gene expression. (10th November 2021) - Reddon, A. R.; Aubin‐Horth, N.; Reader, S. M.
Abstract: Intraspecific variation in social behaviour is often observed among animal populations. Local predation risk can be a key driver of these differences, with populations that are exposed to greater threat typically showing greater aggregation and reduced intraspecific aggression. The Trinidadian guppy, Poecilia reticulata, is found in populations that vary dramatically in predation risk and show greater grouping and reduced agonism in high‐predation populations compared to low‐predation populations. The neurohormonal mechanisms that underpin these differences in behaviour across populations remain unknown and elucidating these mechanisms may help us to understand the evolution of behavioural diversity in this species. We predicted that guppies naturally exposed to higher predation risk would show greater expression of the isotocin system and reduced expression of the vasotocin system when compared to low‐predation fish, because these peptides are thought to promote gregariousness and aggressivity respectively. We collected guppies of both sexes from high‐ and low‐predation sites, replicated in two different Trinidadian rivers, and measured the brain gene expression of isotocin and vasotocin along with their central receptors. Contrary to our prediction, we found that high‐predation guppies showed greater expression of vasotocin, while we did not find evidence that the populations differed in isotocin expression, nor in the expression of the receptors. These results support the hypothesis that vasotocin may act as a neural substrate for social variation in fishes but call into question generalisations about its specific role across species. Abstract : The guppy, Poecilia reticulata, shows more grouping and reduced aggression in populations exposed to high predation risk compared to low predation populations. The mechanisms that underpin these differences remain largely unknown. We predicted that guppies exposed to lower predation risk would show greater expression of the nonapeptide vasotocin compared to the low predation fish, because vasotocin is thought to promote aggression in fishes. We collected guppies from high and low predation sites and measured the brain‐gene expression of vasotocin. Contrary to our prediction, we found that high predation guppies showed greater expression of vasotocin, supporting the hypothesis that vasotocin plays a role in regulating social behaviour in fishes, but casting doubt on generalisations about the specific effects.